ANTI-BACTERIAL ACTIVITY OF ETHANOL EXTRACT OF INDIAN BORAGE (Coleus Amboinicus) LEAVES AGAINST BACILLUS CEREUS - Mutia, Maya Sari; Annisa, Elvia; Suhartomi, Suhartomi (Universitas Tadulako, 2021)
Bacillus cereus is aerobic, positive gram, and spore-forming bacilli bacteria. The enterotoxin of this bacteria can cause food poisonous that manifest as diarrhea and vomitus. Some previous study has been performed to explore the antibacterial effect of Indian borage leaf, but none of them were explore the antibacterial effect of Indian borage against Bacillus cereus. Hence this study was design to explore the antibacterial activity of ethanol extract of Indian borage against Bacillus cereus. This was an experimental study with post only control group design. Ethanol extract was extracted by maceration methods and antibacterial activity against Bacillus cereus was evaluated by disc diffusion methods. The obtained ethanol extract was dissolved into some concentraions (1 g/ml, 0.8 g/ml, 0.6 g/ml, 0.4 g/ml, 0.2 g/ml). Data was analysed by One Way ANOVA and followed by Post hoc Test Tukey HSD using SPSS 25. Ethanol extract of Coleus amboinicus showed significant difference at the two highest concentration group against the lowest concentration (P- Value < 0.05). The average of inhibition zone diameter from the lowest (0.2 gr/ml) and highest (1.0 gr/ml) concentration were 14.87 mm and 31.50 mm, respectively. Overall, ethanol extract of Indian borage leaves had potential antibacterial activity against Bacillus cereus. This antibacterial activity increase followed by the increase of the concentration.